2001
DOI: 10.1107/s0108768101009624
|View full text |Cite
|
Sign up to set email alerts
|

Self-association and stereochemistry study of 2-methylthio-, 2-dimethylaminocyclohexanone oximes and the parent cyclohexanone oxime

Abstract: X-ray diffraction analyses of 2-substituted cyclohexanone oximes C5H9(X)C=NOH [X = SMe (1), NMe2 (2)] and of the parent compound [X = H (3)] showed that their cyclohexyl rings are in a slightly distorted chair conformation. These compounds assume in the solid state the (E) configuration bearing the 2-substituents in the axial conformation. Compounds (1) and (2) exist as dimeric and polymeric hydrogen-bond associates, respectively. Low-temperature X-ray analysis of the cyclohexanone oxime (3) showed that the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…), and the infrared and Raman spectra of cyclohexanone oxime and ϵ caprolactam (supported by density functional theory (DFT) calculations) have been reported as part of the measurement of thermodynamic properties (heats of sublimation and vaporization, and the standard entropy) in the ideal gas state . Infrared spectroscopy has also been used to study hydrogen bonding in cyclohexanone oxime, both in solution and in the solid state . Nonetheless, vibrational spectra have been assigned using normal coordinate analysis and DFT, invoking the isolated molecule approximation so that hydrogen bonding is omitted or only treated empirically – even when the experimental data is for the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…), and the infrared and Raman spectra of cyclohexanone oxime and ϵ caprolactam (supported by density functional theory (DFT) calculations) have been reported as part of the measurement of thermodynamic properties (heats of sublimation and vaporization, and the standard entropy) in the ideal gas state . Infrared spectroscopy has also been used to study hydrogen bonding in cyclohexanone oxime, both in solution and in the solid state . Nonetheless, vibrational spectra have been assigned using normal coordinate analysis and DFT, invoking the isolated molecule approximation so that hydrogen bonding is omitted or only treated empirically – even when the experimental data is for the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated IR intensity of these modes is rather high (Table 10), but no high-intensity band is observed in the wavenumber range of (400 to 500) cm -1 . The possible cause of this fact is the absence of the CHO molecules without a hydrogen bond both in the crystal 22 and in the CCl 4 solution. Therefore, for these modes, the calculated values of the frequencies were used.…”
Section: Journal Ofmentioning
confidence: 99%
“…The infrared spectroscopic study of cyclohexanone oxime showed to be a trimer in the solid state and a dimmer in CCl 4 solution observing the OH stretching vibrational modes of the free and associated forms [9]. 13 C NMR spectroscopic study [10] of cyclohexanone oxime showed the 13 C chemical shifts of 160.…”
Section: Introductionmentioning
confidence: 97%